BCOR Internal Tandem Duplication in High-grade Uterine Sarcomas. (March 2018) - Mariño-Enriquez, Adrián; Lauria, Alexandra; Przybyl, Joanna; Ng, Tony L.; Kowalewska, Magdalena; Debiec-Rychter, Maria; Ganesan, Raji; Sumathi, Vaiyapuri; George, Suzanne; McCluggage, W. Glenn; Nucci, Marisa R.; Lee, Cheng-Han; et al.
Abstract : Endometrial stromal sarcomas (ESSs) are mesenchymal uterine tumors characterized by recurrent genetic events, most commonly chromosomal rearrangements, that create oncogenic gene fusions. High-grade endometrial stromal sarcomas (HG-ESSs), as defined in the 2014 World Health Organization Classification, typically contain oncogenic YWHAE-NUTM2 fusions; however, although not well characterized, there are tumors morphologically overlapping with HG-ESS that do not contain the YWHAE-NUTM2 fusions. These fusions are also found in certain pediatric primitive sarcomas, including clear cell sarcoma of the kidney and soft tissue undifferentiated round cell sarcoma of infancy. A subset of these same pediatric sarcomas lack YWHAE-NUTM2 fusions and instead have internal tandem duplications (ITDs) involving exon 15 of BCOR ( BCOR ITD). We investigated the presence of BCOR ITD by targeted sequencing in a series of 31 uterine sarcomas, comprising 5 low-grade ESS, 13 uterine sarcomas diagnosed as HG-ESS, and 13 undifferentiated uterine sarcomas. BCOR ITD were present in 1 uterine sarcoma diagnosed as HG-ESS and 2 undifferentiated sarcomas with uniform nuclear features, all of which lacked any of the recurrent chromosome translocations known to occur in ESS. These 3 high-grade sarcomas with BCOR ITD affected young patients (average age, 24) and morphologically were composed of nonpleomorphic spindle cells admixed with epithelioid and round cell areas. Focal myxoid stroma was present in 2 cases. Mitotic activity was brisk, necrosis was present, and there was lymphovascular involvement in all cases. The 3 uterine sarcomas with BCOR ITD exhibited diffuse cyclin D1 immunohistochemical expression and there was diffuse BCOR expression in the 2 cases tested. Long-term follow-up in 2 patients revealed 1 to be tumor-free after 22 years and the other to die of disease after 8 years. In conclusion, BCOR ITD is an oncogenic alternative to YWHAE-NUTM2 fusion in high-grade uterine sarcomas with uniform nuclear features. We propose that neoplasms with the morphology described and BCOR ITD be regarded as a unique subtype of high-grade uterine sarcoma, possibly within the family of endometrial stromal neoplasia.